2009
DOI: 10.1182/blood-2009-08-237651
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of serum immunoglobulin abnormalities up to 9.8 years before diagnosis of chronic lymphocytic leukemia: a prospective study

Abstract: Immune-related deficiencies are wellknown complications of chronic lymphocytic leukemia (CLL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 28 publications
5
56
2
2
Order By: Relevance
“…Additionally, in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial, a polyclonal increase in the serum FLC concentration was associated with an increased risk of chronic lymphocytic lymphoma (CLL). This association was present up to 9 years prior to the diagnosis of CLL but became stronger closer to the time of diagnosis (14 ).…”
Section: Polyclonal Flcs As a Clinically Relevant Biomarkermentioning
confidence: 86%
“…Additionally, in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial, a polyclonal increase in the serum FLC concentration was associated with an increased risk of chronic lymphocytic lymphoma (CLL). This association was present up to 9 years prior to the diagnosis of CLL but became stronger closer to the time of diagnosis (14 ).…”
Section: Polyclonal Flcs As a Clinically Relevant Biomarkermentioning
confidence: 86%
“…protein electrophoresis, respectively. In stored prediagnostic blood from 109 persons who subsequently developed CLL, the prevalence of an abnormal FLC ratio, Mprotein, and hypogammaglobulinemia before CLL diagnosis was 38% (95% confidence interval, 29%-47%), 13% (7%-21%), and 3% (1%-8%), respectively (58). In fact, Mproteins and abnormal FLC ratios were detected up to 9.8 years before CLL diagnosis in a total of 48 persons (44%).…”
Section: Future Directionsmentioning
confidence: 96%
“…Hypogammaglobulinemia was not present until 3 years before the diagnosis of CLL. Among 37 patients with information on tumor cell immunophenotype, an association between immunophenotype and involved FLC (P ¼ 0.024) was observed (58). Prospective studies on the natural history of coexisting MBL and monoclonal gammopathies should help illuminate the complex relationships among B-cell malignancies and their precursors.…”
Section: Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study of eight chronic lymphocytic leukemia (CLL) patients, an Mprotein was detectable in six individuals only by the serum FLC assay and not by standard SPEP/IFE [29]. A prospective study found that FLC levels may be abnormal nearly 10 years before a diagnosis of CLL is made, suggesting that their production may represent an early event in the pathogenesis of the disease [30]. Other emerging data suggest that an abnormal FLC ratio confers a worse prognosis in CLL patients, and may actually identify a biologically distinct subgroup of the disease [31,32].…”
Section: Clinical Applicationsmentioning
confidence: 99%